Potential Cultural Value of Ceramic and Pottery Findings, Talang Pangeran Village, Ogan Komering Ilir - Muhamad Idris; Yan Aditiya Pratama; Richard Saputra; Gema Tahta Anugrah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Talang Pangeran Village, Ogan Komering Ilir Regency, stores historical data and information from the classical period of Young Hindu-Buddhist to the colonial period. This information needs to be supported by accurate data to support the theory about the local culture of Ogan Komering Ilir which has existed for hundreds of years. The research problems are: The formulation of the problem in this study: how was the potential cultural value of the typology of ceramics and pottery surface survey findings in Talang Pangeran village, Ogan Komering Ilir. The purpose of the study was to determine the typology of ceramics and pottery from surface survey findings in Talang Pangeran Village, Ogan Komering Ilir. The benefit of the study was the availability of data and information about the typology of ceramics and pottery from Talang Pangeran village. To collect data and analyze data, this study used a qualitative methodology with a surface survey approach. Data collection techniques with field observations, in-depth interviews and document collection. The result of this study stated that Talang Pangeran Village, Ogan Koring Ilir district, stored important historical data and information in the preparation of local history of South Sumatra. This area had historical data on political and economic relations with West Java, China, Europe and Palembang.